GUARANÍ AQUIFER SYSTEM (GAS) VULNERABILITY EVALUATION WITHIN THE TACUAREMBÓ MUNICIPALITY SURROUNDINGS, URUGUAY: APPLICATION OF THE GOD AND DRASTIC METHODS - Carrión, Roberto; Gastmans, Didier [UNESP]; Veroslavsky, Gerardo (Derbyana, 2024)
The sustainability of the water resources is of utmost importance, whether surface or groundwater. This work addresses the protection of the Guaraní Aquifer in the Tacuarembó municipality, capital of the homonymous department in Uruguay. Evaluating the intrinsic vulnerability and the risk of contamination of the aquifer provided the necessary knowledge to plan its use. It should also be considered in the territorial planning plans in that city to manage the resources better. GOD and DRASTIC methods were applied to determine vulnerability. The application of these methods showed differences in vulnerability determinations since the first takes fewer parameters for its evaluation than those considered by the second. However, applying one or the other depends mainly on the data and information available in the area under study. It was observed that the GOD method is more restrictive than DRASTIC: in the first, it considers that 24.3% of the area has a high vulnerability, while DRASTIC considers it 16.8%; in the case of moderate GOD classifies 56.2% as such, while DRASTIC classifies it at 76.3%. Regarding the area occupied by the low vulnerability of the area, DRASTIC is somewhat less restricted than GOD since the former covers an area 6.8% larger, while GOD restricts it to 19.6%.
EVALUACIÓN DE LA VULNERABILIDAD DEL SISTEMA ACUÍFERO GUARANÍ (SAG) EN LOS ALREDEDORES DE LA CIUDAD DE TACUAREMBÓ, URUGUAY: APLICACIÓN DE LOS MÉTODOS GOD Y DRASTIC
Keywords: Guaraní Aquifer System; Hydrogeology; Uruguay; Vulnerability